THE EVALUATION OF KNOWLEDGE AND BEHAVIOR IN HYGIENE SANITATION OF FOOD HANDLERS AT AJI SANTOSO INTERNATIONAL FOOTBALL ACADEMY - Fitriah, Arsinah Habibah; Heranisa, Audra; Winarni, Sri (HEARTY, 2024)
The quality of food service is influenced by the knowledge of hygiene and sanitation (NHS) and the hygiene and sanitation behavior (PHS) of food handlers. NHS and PHS are essential for controlling the risk factors of contamination. This research aims to assess the NHS and PHS of food handlers at Aji Santoso International Football Academy (ASIFA). This was a descriptive study with a cross-sectional design, utilizing the total population sampling method. The sample size was seven individuals. The data were analyzed descriptively. The characteristics of the samples included individuals within the productive age range of 15–64 years, with 57% male and 43% female. Educational backgrounds were 72% high school, 14% elementary school, and 14% higher education. The work experience of the samples indicated that 43% had worked for 5 years. The results showed that the good value of NHS did not align with PHS values, as evidenced by 100% of food handlers having inadequate PHS values. Therefore, training to improve both NHS and PHS among food handlers at ASIFA was deemed necessary.